PENERAPAN MODEL PEMBELAJARAN THINK PAIR SHARE BERBANTUAN MEDIA LEAFLET DILENGKAPI LKS TEKA-TEKI SILANG UNTUK MENINGKATKAN HASIL BELAJAR SISWA DI SMP NEGERI 3 WAINGAPU - Rambu Wuakaranu, Destri; Makaborang, Yohana; Ndjoeroemana, Yohana (Jurnal Biogenerasi, 2025)
The purpose of this study was to describe the cognitive and affective learning outcomes of students and the improvement of learning outcomes at SMP Negeri 3 Waingapu after implementing the Think Pair Share model assisted by Leaflet media equipped with LKS Crossword puzzles. The research data were obtained from the results of questionnaires, interviews, and assessments of student learning outcomes. The research method used was Classroom Action Research (CAR) involving 30 students. The results of the study showed a significant increase with the percentage of student learning outcomes completion in the pre-cycle of 27%, increasing by 50% in cycle I, then increasing to 83% in cycle II. Thus, it can be concluded that the use of the Think Pair Share model combined with Leaflet media and equipped with LKS Crossword puzzles can improve learning outcomes and students' cognitive and affective abilities in science lessons.